Utterly Otterly Day - Casanova, Mary; Hoyt, Ard (New York : Simon & Schuster Books for Young Readers, 2008)
After a day out on his own, Little Otter realizes that he still needs his family no matter how big he grows.
Keywords: Otters -- Fiction